Hemodialysis catheter heparin lock related bleeding: Hemorrhagic shock every other day. Issue 3 (May 2022) - Marques, Joana; Duarte, Tiago Isidoro; Cotovio, Patrícia; Borges, André; Germano, Nuno
Catheter dysfunction is an important cause of catheter loss. In order to prevent this, locking solutions with minimal risk of systemic anticoagulation are used to ensure catheter patency. At present the most commonly used solutions are either heparin or sodium citrate. According to the literature use of sodium citrate may be advantageous in reducing bleeding events. We report a case of hemorrhagic shock following hemodialysis catheter lock with heparin, reversed after switching solution to sodium citrate.